Indigenous Knowledge and Community Ecological Governance: Lessons from Empirical Cases - Musah, Alhassan (Journal of Contemporary Social Science and Education Studies (JOCSSES) E-ISSN- 2785-8774, 2023)
This paper uses theoretical and empirical experiences from different contexts to discuss the intrinsic value of indigenous and local ecological knowledge, and their implications for sustainable development and environmental justice. Specifically, the study deduces lessons on how indigenous local knowledge has been deployed by farmers and communities in Northern Guatemela, Papua New Guinea, Nepal and Ghana to protect critical ecosystems and enhance environmental integrity. This paper employs review writing investigation and evidence from existing theoretical and empirical examinations, to explore the relevance of indigenous and local knowledge in sustainable biodiversity management. The study concludes that indigenous and local knowledge is valuable and has proven to have supported farmers in sustainable farm practices, building resilience against climate change, and preventing anthropogenic forces which could have otherwise led to extinction of particular and significant biodiversity and local resources. From first-hand experience of its potency, some scholars have tended to equate indigenous knowledge to Western scientific knowledge. Rather than equating indigenous knowledge to Western scientific knowledge, we call for practical ways of enhancing complementarity and synergy between the two genres of knowledge.